2018
DOI: 10.1007/5584_2018_167
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder: A Review of Therapeutic Role of Meditation Interventions

Abstract: This review is an attempt to provide a comprehensive view of post-traumatic-stress disorder (PTSD) and its therapy, focusing on the use of meditation interventions. PTSD is a multimodal psycho-physiological-behavioral disorder, which calls for the potential usefulness of spiritual therapy. Recent times witness a substantial scientific interest in an alternative mind-to-body psychobehavioral therapy; the exemplary of which is meditation. Meditation is a form of mental exercise that has an extensive, albeit stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
2
0
2
Order By: Relevance
“…PTSD is a global health issue and has a serious negative impact on individuals and society, the prevalence of PTSD is high and it substantially increases the risk of other psychiatric morbidities as well as medical disorders ( 2 4 ). Although the current studies have identified the molecular, neurochemical and genetic abnormalities associated with of PTSD ( 5 ), prevention and treatment of PTSD are limited ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is a global health issue and has a serious negative impact on individuals and society, the prevalence of PTSD is high and it substantially increases the risk of other psychiatric morbidities as well as medical disorders ( 2 4 ). Although the current studies have identified the molecular, neurochemical and genetic abnormalities associated with of PTSD ( 5 ), prevention and treatment of PTSD are limited ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic stress disorder: a review of therapeutic role of meditation interventions 20 Revisão de literatura que indicou benefícios da meditação em distúrbios de stress póstraumático através do cultivo de consciência, alterações de comportamento e alteração das experiências emocionais.…”
Section: Mindfulnessunclassified
“…Outro estudo sugeriu a utilização da meditação para alívio dos sintomas e como tratamento -unido a farmacoterapia e de maneira isolada -dos distúrbios póstraumáticos, tendo em vista a ausência de orientação e ampla disponibilidade de medicamentos utilizados, como por exemplo, os inibidores da recaptação de serotonina, inibidores da monoamina oxidase e antidepressivos tricíclicos 20 .…”
Section: Medicamentos E Meditação: As Relaçõesunclassified
See 1 more Smart Citation